2010
DOI: 10.1103/physrevb.82.245415
|View full text |Cite|
|
Sign up to set email alerts
|

Thermopower of multilayer graphene

Abstract: We systematically calculate thermopower of biased and unbiased multilayer graphene systems. The effect of screening to a bias field perpendicular to the graphene planes is taken into account selfconsistently under the Hartree approximation. The model including nearest neighbor hopping and the more general Slonczewski-Weiss-McClure (SWMcC) model are both considered for a comparison. The effect of impurity scattering is studied for monolayer and unbiased bilayer graphene and is treated in terms of the self-consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…If a band gap of 288 meV is induced in a bilayer system by an external vertical field, it has been calculated that the room temperature thermopower is enhanced by a factor of more than 4 compared with that of monolayer graphene and gapless bilayer graphene [87]. A quite systematic study of multilayer graphene has shown that the largest thermopower is actually achieved in biased bilayer graphene [88]. Regarding the effect of bandgap, it is worth mentioning the work of Sharapov et al based on Kubo calculations showing that in certain conditions, a small bandgap of about 10 meV, e.g.…”
Section: Theory and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…If a band gap of 288 meV is induced in a bilayer system by an external vertical field, it has been calculated that the room temperature thermopower is enhanced by a factor of more than 4 compared with that of monolayer graphene and gapless bilayer graphene [87]. A quite systematic study of multilayer graphene has shown that the largest thermopower is actually achieved in biased bilayer graphene [88]. Regarding the effect of bandgap, it is worth mentioning the work of Sharapov et al based on Kubo calculations showing that in certain conditions, a small bandgap of about 10 meV, e.g.…”
Section: Theory and Simulationmentioning
confidence: 99%
“…The thermopower of bilayer and multilayer graphene has been studied in different works [87][88][89][90]. Under a magnetic field, the disorder-induced broadening of Landau levels has been shown to have in bilayer graphene an effect similar to that in monolayer graphene.…”
Section: Theory and Simulationmentioning
confidence: 99%
“…Model systems play a prominent role in Kohn-Sham (KS) 1 density functional theory (DFT) 2 , due to their utility in understanding and guiding the development of physically sound and accurate exchange-correlation (XC) functionals, which shall include quantum effects of the many-electron interaction. Thus, over the years, a wide number of model systems has been considered within DFT 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Zinc orthotitanate, Zn 2 TiO 4 (ZTO) has important physical, electrical and optical properties, has a good transmittance in visible light, and can be used for solar cell window electrode. ZTO has higher thermal stability than single metal oxide ZnO [6]. But now there is little research of ZTO as solar cell electrode.…”
Section: Introductionmentioning
confidence: 99%